Teaching Arabic language in Islamic schools for non-Arab: A Singaporean perspective - Hj. Yaakub, Muhamadul Bakir; Muhamad Ramlan, Siti Rafiah (2013)
The teaching of the Arabic language in society as a society Singapore is not an easy one. This fact is observable from various issues and complaints debated in the dialogues occurred among people whom had a good concern on the future of this language and teaching this subject matter to this community in the contemporary challenging context, especially with the obvious drop in term of learner reception, academic performance and interest toward learning this language, plus their complaint on the difficulties in learning and acquiring this language up to the level of using in their daily life. In this sense, this study describes the overall impression of Singaporean society toward the future of teaching Arabic language in Singaporean Islamic schools, and discloses its contemporary public impression. In order to achieve this objective, a brief historical overview of this community and its engagement with Arabic language was presented and elaborated especially to understand the current situation together with its economical achievement and globalization. A survey was distributed to 50 respondents sample together with structured interview with some important personalities related to educational practices. The data was statistically analysed using SPSS to measure the perception of the Singaporean community toward the current status of learning Arabic language and its future regardless of differences in its objectives such as religiosities, trades, and tourisms.